Paper gai : boletin informativo del Col.lectiu Lambda. (Valencia : Col.lectia Lambda de Gais i Lesbianes, 1991)
Fonds Suzan Daniel (FSD)
Periodiciteit: tweemaandelijks
Redactie: C/Valencians 6, 46001 Valencia
Spaans
Periodiek